Learning to Embody Leadership Through Mindfulness and Somatics Practice. (August 2016) - Brendel, William; Bennett, Carmela
The Problem: Given the unpredictable nature of organizational life, leadership development programs that rely primarily on cognitive processing and critical reflection are no longer sufficient. What is required is an integrated pedagogy that enables individuals to access and embody a "way of being, " an aligned presence and purpose that spans all contexts so that the individual and leader are not separate entities but rather a fully cohesive self. To develop this capacity, reputable organizations are experimenting with holistic learning methodologies, including mindfulness and somatics practices. However, these methodologies have yet to be fully grounded in adult learning and leadership best practices, empirical research, mind–body principles, and leadership performance. The Solution: Through a critical review of relevant theory, practice, and empirical research, this article conceptualizes a constructive developmental learning methodology, which integrates mindfulness and somatics practices that transform a leader's relationship with behavior from the automatic to the consciously chosen realm. The article presents a practical model of embodied leadership where individuals learn ways to deepen awareness to include both the mind and body as an interdependent system to remain open, grounded, and engaged in a way that builds resilience, and resourcefulness, and improves relationships in complex environments. The Stakeholders: Human resource development professionals, executive coaches, and aspiring leaders seek a holistic and practical leadership development approach, which is conceptually and empirically linked to leadership and organizational performance.